2018
DOI: 10.1089/cell.2018.0001
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylase Inhibitor, CI994, Improves Nuclear Reprogramming and In Vitro Developmental Potential of Cloned Pig Embryos

Abstract: Epigenetic reprogramming and somatic cell nuclear transfer (SCNT) cloning efficiency were recently enhanced using histone deacetylase inhibitors (HDACis). In this study, we investigated the time effect of CI994, an HDACi, on the blastocyst formation rate, acetylation levels of H3K9 and H4K12, DNA methylation levels of anti-5-methylcytosine (5mC), and some mRNA expression of pluripotency-related genes in pig SCNT embryos. Treatment with 10 μM CI994 for 24 hours significantly improved the blastocyst formation ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Porcine somatic cell nuclear transfer (SCNT) is a required tool for human disease modelling to study pig‐to‐human xenotransplantation and for the improvement and breeding of disease‐resistant pig strains (Nagashima & Matsunari, ; Samiec & Skrzyszowska, ). The efficiency of SCNT in pigs is affected, to the highest degree, by factors such as (a) nuclear (meiotic), epigenomic and cytoplasmic maturity of nuclear recipient oocytes (Samiec & Skrzyszowska, ; Wang et al, ; Xu, Qian, Si, Qu, & Li, ); (b) epigenetic reprogrammability of somatic cell‐inherited nuclear genome (Jin et al, , ; Samiec & Skrzyszowska, ); (c) capability of nuclear‐transferred (NT) oocytes to be artificially activated (De Macedo et al, ; Samiec & Skrzyszowska, , ); (d) intergenomic communication between nuclear and mitochondrial compartments in NT oocytes and resultant cloned embryos (Estrada et al, ; Opiela, Samiec, & Romanek, ; Samiec, , ); and (e) incidence of apoptotic cell death in nuclear donor cells and cloned embryos (Ju, Rui, Lu, Lin, & Guo, ; Lee et al, ; Samiec & Skrzyszowska, ). In this regard, oocyte maturation at the nuclear, epigenomic and cytoplasmic levels seems to play a pivotal role in determining molecular quality and suitability of nuclear recipient oocytes for SCNT procedure (Jeon et al, ; Lin, Oqani, Lee, Shin, & Jin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Porcine somatic cell nuclear transfer (SCNT) is a required tool for human disease modelling to study pig‐to‐human xenotransplantation and for the improvement and breeding of disease‐resistant pig strains (Nagashima & Matsunari, ; Samiec & Skrzyszowska, ). The efficiency of SCNT in pigs is affected, to the highest degree, by factors such as (a) nuclear (meiotic), epigenomic and cytoplasmic maturity of nuclear recipient oocytes (Samiec & Skrzyszowska, ; Wang et al, ; Xu, Qian, Si, Qu, & Li, ); (b) epigenetic reprogrammability of somatic cell‐inherited nuclear genome (Jin et al, , ; Samiec & Skrzyszowska, ); (c) capability of nuclear‐transferred (NT) oocytes to be artificially activated (De Macedo et al, ; Samiec & Skrzyszowska, , ); (d) intergenomic communication between nuclear and mitochondrial compartments in NT oocytes and resultant cloned embryos (Estrada et al, ; Opiela, Samiec, & Romanek, ; Samiec, , ); and (e) incidence of apoptotic cell death in nuclear donor cells and cloned embryos (Ju, Rui, Lu, Lin, & Guo, ; Lee et al, ; Samiec & Skrzyszowska, ). In this regard, oocyte maturation at the nuclear, epigenomic and cytoplasmic levels seems to play a pivotal role in determining molecular quality and suitability of nuclear recipient oocytes for SCNT procedure (Jeon et al, ; Lin, Oqani, Lee, Shin, & Jin, ).…”
Section: Introductionmentioning
confidence: 99%
“…We focused on H3K27ac, a known marker of active enhancers that is enriched at activity-dependent regulatory elements after neuronal activation (30, 42, 52-54), correlates with gene transcription (30,55) and often co-occurs with H3K9ac, a marker of active promoters (56). Furthermore, in line with previous studies (15,25,57,58), we found that HDACi treatment increased global H3K27ac, alongside H3K9ac and H4K12ac as revealed by western blotting (Two-way ANOVA, F(3,60) = 22.47, P = 1.11e-13) (Supplemental Fig. 11).…”
Section: Hdaci Combined With Cfc Enriches H3k27ac At Genes Involved In Synaptic Communicationmentioning
confidence: 61%
“… 35 The activity of somatic cells undergoing such an operation is significantly reduced, and their nuclear reprogramming ability is affected. 36 Furthermore, it will cause the surrogate sow to miscarry and the fetus to be deformed. Therefore, when preparing porcine-modified somatic cells, it is generally required to use high-activity cells with early generation and short cumulative culture times.…”
Section: Discussionmentioning
confidence: 99%